2005
DOI: 10.1038/sj.jea.7500423
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to trace elements and risk of cutaneous melanoma

Abstract: Purpose: Our aim was to examine the risk of melanoma in association with exposure to trace elements of toxicological and nutritional interest. Methods: We analyzed the concentrations of cadmium, lead, chromium, selenium, copper and zinc in toenails of 58 patients with newly diagnosed cutaneous melanoma as well as in 58 age-and sex-matched control subjects, randomly selected from the population of Modena province in northern Italy. Results: Melanoma risk was substantially unrelated to toenail levels of cadmium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…9 In particular, toenail As concentrations have been shown to be a good biomarker of environmental exposure to As. 1012 The concentration of Cr in toenails has also been used as a biomarker of exposure in epidemiologic studies, 1315 as well as concentrations of Ni in toenails 16 and fingernails, 17 although to a lesser extent than As or Cr.…”
Section: Introductionmentioning
confidence: 99%
“…9 In particular, toenail As concentrations have been shown to be a good biomarker of environmental exposure to As. 1012 The concentration of Cr in toenails has also been used as a biomarker of exposure in epidemiologic studies, 1315 as well as concentrations of Ni in toenails 16 and fingernails, 17 although to a lesser extent than As or Cr.…”
Section: Introductionmentioning
confidence: 99%
“…Within a population-based, case-control study on melanoma risk factors carried out on the residents in Modena Province, northern Italy, we recruited a consecutive series of 59 newly diagnosed melanoma patients attending our Dermatologic Clinic (the only one in the Province) and 59 randomly selected population controls matched to the patients [7,8]. Seventy-two per cent of the newly diagnosed patients with melanoma of the skin agreed to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…141 Small-scale human studies evaluating melanoma incidence with elevated environmental exposure to selenium have shown both positive and negative correlations. 142,143 Vitamin D obtained from the diet and synthesized in the skin in response to UVB exposure has been advocated as a potential preventive agent for prostate, colon, and lung cancers. [144][145][146][147] Recent epidemiologic studies have suggested that sunlight exposure may reduce the risk of non-Hodgkins lymphoma 148 and may be associated with improved survival in patients with early-stage melanoma.…”
Section: Nutrientsmentioning
confidence: 99%